Evaluation of an Anti‐Bullying Program: Student Reports of Knowledge and Confidence to Manage Bullying - Beran, Tanya; Shapiro, Bonnie (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
This research evaluates the effectiveness of an anti‐bullying program, Project Ploughshares Puppets for Peace (Woodfine, Lubimiv, & Langlois, 1995). Students in grades 3 and 4 (N = 129, 69 boys, 60 girls) from two public elementary schools completed a questionnaire on bullying at both pretest/post‐test. Although Chi‐square results showed no significant increase in knowledge or skills to deal with bullying, responses to open‐ended questions indicated that half the students reported feeling more confident in managing bullying. These results suggest that evaluations should include student perspectives on the impact of a program that extends beyond specific program goals. Key words: bullying, peer aggression, program evaluation Cette étude évalue l’efficacité du programme de lutte contre l’intimidation Puppets for Peace de Project Ploughshares (Woodfine, Lubimiv et Langlois, 1995). Des élèves de 3e et 4e années (N = 129, 69 garçons, 60 filles) de deux écoles primaires publiques ont répondu à un questionnaire sur l’intimidation avant et après la mise en œuvre du programme. Bien que les résultats du test chi carré n’indiquent aucune amélioration notable des connaissances et des compétences susceptibles de contrer l’intimidation, les réponses aux questions ouvertes mettent en évidence que la moitié des élèves disent se sentir plus sûrs d’eux‐mêmes face à l’intimidation. Ces résultats semblent indiquer que les évaluations de programmes de prévention devraient inclure les points de vue des élèves sur leur impact, sachant que ces derniers dépassent souvent les objectifs initiaux. Mots clés : intimidation, agression par des pairs, évaluation des programmes.